2015
DOI: 10.1016/j.ccell.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Vulnerability of IDH1 Mutant Cancers to NAD+ Depletion

Abstract: Summary Heterozygous mutation of IDH1 in cancers modifies IDH1 enzymatic activity, reprogramming metabolite flux and markedly elevating 2-hydroxyglutarate (2-HG). Here, we found that 2-HG depletion did not inhibit growth of several IDH1 mutant solid cancer types. To identify other metabolic therapeutic targets, we systematically profiled metabolites in endogenous IDH1 mutant cancer cells after mutant IDH1 inhibition and discovered a profound vulnerability to depletion of the coenzyme NAD+. Mutant IDH1 lowered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
428
5
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(463 citation statements)
references
References 61 publications
28
428
5
2
Order By: Relevance
“…Gene expression and protein analyses indicated that ibrutinib (also used to treat CLL and other lymphomas) unleashes strong upregulation of Nampt which makes these cells more susceptible to NAD + -depleting agents. Overall, as recently described for IDH1 mutant and MYC-overexpressing tumor cells [14,15], our study confirms metabolic pathway as TKI sensitizer. As a result, Nampt-targeting emerges as an effective approach not only when coupled to standard chemotherapy or radiotherapy, as previously reported, but also in patients receiving more modern, molecularly targeted agents, making them more effective (Figure 1).…”
supporting
confidence: 64%
“…Gene expression and protein analyses indicated that ibrutinib (also used to treat CLL and other lymphomas) unleashes strong upregulation of Nampt which makes these cells more susceptible to NAD + -depleting agents. Overall, as recently described for IDH1 mutant and MYC-overexpressing tumor cells [14,15], our study confirms metabolic pathway as TKI sensitizer. As a result, Nampt-targeting emerges as an effective approach not only when coupled to standard chemotherapy or radiotherapy, as previously reported, but also in patients receiving more modern, molecularly targeted agents, making them more effective (Figure 1).…”
supporting
confidence: 64%
“…Targeting NNMT has proven beneficial for protection against diet-induced obesity through regulation of the SIRT1/NAMPT/NAD + pathway (64,74). Given the potential utility of NAMPT inhibitors in some gliomas, future studies may demonstrate the benefit of dual targeting of NNMT and NAMPT for glioma therapy (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT is expressed at high levels in several different cancers and, therefore, this enzyme has been considered a potential therapeutic cancer target (5,9,27). Recent studies in glioblastoma have indicated specific genetic subgroups may be exquisitely sensitive to NAMPT inhibition (28,29). IDH1 mutation sensitizes GSCs to NAMPT inhibitors due to low ambient levels of NAD + , resulting from downregulation of nicotinic acid phosphoribosyltransferase (NAPRT1), which catalyzes an alternative NAD + salvage pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in glioblastoma have indicated specific genetic subgroups may be exquisitely sensitive to NAMPT inhibition (28,29). IDH1 mutation sensitizes GSCs to NAMPT inhibitors due to low ambient levels of NAD + , resulting from downregulation of nicotinic acid phosphoribosyltransferase (NAPRT1), which catalyzes an alternative NAD + salvage pathway (29). MYC overexpression and MYC or N-MYC amplification in glioblastoma cells increase glycolytic flux and lower NAD + levels, similarly leading to increased susceptibility to NAMPT inhibitors (28).…”
Section: Discussionmentioning
confidence: 99%